Component-based estimation of recovery time and time-related expenses after hurricane events - Wei, Zhuoxuan; Pinelli, Jean-Paul; Gurley, Kurtis; Hamid, Shahid; Flannery, Gail (Frontiers in Built Environment, 2024)
Due to hurricane damage, building residents or businesses must be relocated during the recovery time, which leads to time related expenses (TRE), also known as additional living expenses (ALE) or extra expense coverage (EEC) or business interruption insurance (BIC). TRE are difficult to predict since they depend on the damage and time necessary to repair the building as well as on external factors such as damaged utilities and the availability of labor and materials among other issues. The authors developed a new TRE hurricane vulnerability model for mid/high-rise buildings. The model combines estimates of repair time (Trepair), delay time (Tdelay) and utilities downtime (Tdown) to predict overall recovery time (Treco). The outputs of the model include: 1) TRE vulnerability matrices, which yield probabilities of Trepair, Tdelay, Tdown, Treco, and TRE conditional on either maximum 3-sec wind speed or overall building damage ratio; 2) the corresponding vulnerability curves, which yield the mean values as a function wind speed or damage ratio. Insurers can use these results to project TRE and emergency managers and urban planners can use the recovery times to characterize the resilience of coastal communities. The paper summarizes the methodology and illustrates the implementation and results. Selected results of Treco are compared with the recovery times provided by the HAZUS-MH hurricane model.